TREN PENELITIAN GLOBAL TERKAIT PENGGUNAAN REGRESI LINEAR DALAM SISTEM PENDIDIKAN: ANALISIS BIBLIOMETRIK (2010–2025) - Nanik Tri Purwaningsih; Anastasia Abubakar; Suparman Suparman (CV. Denasya Smart Publisher, 2026)
This study aims to map and analyze global trends in the use of Linear Regression in Education Systems quantitatively, including publication counts, citations, author collaboration patterns, institutional affiliations, and country contributions. Publication data from the Dimensions database covering 2010–2025 were analyzed using bibliometric methods with VOSviewer, while literature selection followed the PRISMA framework to ensure validity and transparency. The results revealed 2,987 publications with a total of 12,647 citations, showing a significant increase since 2017, particularly in the fields of Education Systems, Education, and Curriculum and Pedagogy. Network, overlay, and density visualizations confirmed Linear Regression as a central method in Educational research, closely related to teacher performance, student learning outcomes, and engagement. Although researcher collaboration remains fragmented, the dominance of quantitative and computational journals demonstrates the wide and interdisciplinary application of Linear Regression, including integration with digital learning and financial literacy. These findings highlight the relevance of Linear Regression in evidence-based Educational research and suggest opportunities for advancing analytical methods and international collaboration in the future.